Non-Alkaloidal Compounds from Khat (Catha edulis) Leaves - Tsegu Kiros (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2020)
Khat belongs to the family Celastraceae, genus Catha, and species edulis. More than 200 compounds have previously been identified in Khat leaves, including: 40 alkaloids, terpenoids and sterol, flavonoids, glycosides, tannins, amino acids, vitamins and minerals. Researchers have spent their effort and time merely on study of the alkaloidal components (mainly the stimulant agents, cathinone and cathine) of Khat both qualitatively and quantitatively. The two principal Khat stimulant compounds, cathinone and cathine, by now are well established. But, on the contrary, previous studies on the non-alkaloidal constituents of the plant were limited. The objective of this work was therefore to isolate and characterize compounds from non-alkaloidal fractions of the plant’s leaves. In this work, two non-alkaloidal compounds (KNA-1 and KNA-2) were isolated and characterized from the acid-EtOAc extract of fresh and oven-dried leaves of Khat (Catha edulis). From the present study, it is possible to conclude that investing more effort and time on searching additional non-alkaloidal principles from the leaves of Khat is so necessary. And further works could be done in the future to isolate extra non-alkaloidal compounds from the leaves and other parts of Khat and evaluate their biological activity.